Clinical characteristics and management of clinically amyopathic juvenile dermatomyositis across four academic centers - BARIŞ, HATİCE EZGİ (WILEY, 2021)
Background/Objectives: Clinically amyopathic juvenile dermatomyositis (CAJDM) is an uncommon but important subset of patients with juvenile dermatomyositis, characterized by pathognomonic cutaneous findings without clinically evident muscle weakness. With limited data available and lack of standardized management guidelines for CAJDM, we sought to describe common features, including early indicators that may be associated with progression of muscle disease, and review the course and treatment of these patients. Methods: A retrospective chart review of patients with CAJDM was conducted at four North American academic centers between the years 2000 and 2015. Results: Twenty-nine patients were included, of whom 21 (72%) were female. After a median follow-up of 4 years (IQR 1.8-5.8 years), 5 of the 29 (17%) patients with CAJDM evolved into classic juvenile dermatomyositis. Median time to develop weakness was 12 months (IQR 8-19 months) after diagnosis. The skin disease of CAJDM patients who did not develop weakness was often found to be recalcitrant with 58% of them requiring multiple systemic therapies to control their cutaneous disease. Conclusion: These results highlight the need for long-term monitoring for the development of myositis in CAJDM and for prospective studies on treatment of recalcitrant skin disease.
Keywords: clinically amyopathic juvenile dermatomyositis; collagen vascular disorders; inflammatory disorders; skin signs of systemic disease; therapy-systemic; therapy-topical; IDIOPATHIC INFLAMMATORY MYOPATHIES; CUTANEOUS ASSESSMENT-TOOL; MYOSITIS; CHILDREN; VALIDATION